Review on OFDM based Image Transmission System - Vasanth Kumar T. R, Vashanth; V. Prasad, K (International Journal of Engineering and Technology, 2018)
Growing interest in the wireless communication technologies has been focusing on meeting the demands of consumers with respect to quality of communication in image transmission. Thus, most of the researches were giving prior interest towards providing better channel capacity, maximized transmission rate and low interference. An orthogonal frequency division multiplexing (OFDM) can offer higher bandwidth and interference-free signal transmission. Thus, the transmitted image over OFDM can have optimal image quality at the receiver end. The current researches indicated that the OFDM concept could provide satisfactory communication performance for next-generation wireless communication standards. This paper intends to discuss the investigational research on the OFDM technology for image transmission exist with respect to different approaches like Simulink, FPGA technology, etc. and the significance of current research contributions. Finally, the future line of research is illustrated to overcome the research gaps.Â